The Legal Landscape: A Comparative Examination of Religious Blasphemy Enforcement in Egypt and Indonesia - AR, Zulfahmi; Wahidin, Wahidin; Haq, Islamul (DIKTUM: Jurnal Syariah dan Hukum, 2023)
The objective of this study is to ascertain the comparative analysis of religious blasphemy legislation in Egypt and Indonesia. This study also elucidates the implementation of religious blasphemy legislation in Egypt and Indonesia. This study involves comparative legal research. Comparative research was conducted to gather additional insights on the blasphemy laws in Egypt and Indonesia. This study employs library research methodology to gather both primary and secondary data. The findings of this study indicate that the legislation governing religious blasphemy in Indonesia is law number. 1/ PNPS/1965, but in Egypt it is article 98 of the Egyptian Penal Code. Additionally, this study discovered parallels in the implementation of religious blasphemy legislation in Egypt and Indonesia. The implementation of anti-blasphemy legislation in both nations frequently subjects defendants to a succession of grave human rights infringements perpetrated by both private individuals and government agents